Do penalties matter? The impact of the introduction of financial penalties in the United Kingdom for insider trading. Issue 24 (20th May 2020) - Gilbert, Aaron; Tourani-Rad, Alireza
ABSTRACT: Insider trading is widely thought to be rampant, resulting in considerable harm to financial markets despite efforts to deter insiders. The main tools to deter insider trading are the sanctions imposed by legislators, of which financial penalties are one type. Civil financial penalties come with a lower burden of proof, which may increase deterrence given the circumstantial nature of insider trading. However, financial penalties have been largely overlooked globally. We test the deterrence of civil financial penalties around the introduction of unlimited financial sanctions for insider trading in the UK in December 2001. We employ three measures of informed trading and two measures of price efficiency for 412 UK listed companies around 12 months either side of the enactment of the financial penalties. We observe evidence that financial penalties have generally increased the deterrence of insiders in the UK market.